Interpreting Semitic Protolanguage as a Conlag a Constructed Language (Global Journal of Human-Social Science, 2013)
One of the most natural approaches to the problem of origins of natural languages is the study of hidden intelligent communications emanating from their historical forms Semitic languages history is especially meaningful in this sense One discovers in particular that Biblical Hebrew BH the best preserved fossil of the Semitic protolanguage is primarily a verbal language with an average verse of the Hebrew Bible containing no less than three verbs and with the biggest part of its vocabulary representing morphological derivations from verbal roots almost entirely triliteral the feature BH shares with all Semitic and a few other Afro- Asiatic languages For classical linguists more than hundred years ago it was surprising to discover that verbal system of BH is as we say today optimal from the Information Theory s point of view and that its formal topological morphology is semantically meaningful These and other basic features of BH reflect in our opinion the original design of the Semitic Protolanguage and suggest the indispensabilityof IIH Inspirational Intelligence Hypothesis our main topic for the understanding of origins of natural languages Our project is of vertical nature with respect to the time in difference with the vastly dominating today horizontal linguistic approaches
Keywords: semitic languages; protolanguage; verbal system; origins of natural languages; artificial intelligence; intelligent communi-cation; conlag or construc